SMEs, Foreign Trade and Indian Economy. - Bihari, Suresh Chandra and Mansimran Kaur (2012)
SME segment is the backbone for any developing economy. They are the blue chips of tomorrow and are the second largest provider of employment in India. SMEs in India have showcased the modern Indian socio-economic policies that include judicious use of foreign exchange reserves for export and import intermediate goods, capital goods, raw materials, merchandise, finished goods etc. These economic units provide employment and utilize the factors of production to be able to reach the optimal level. These units also contribute to collection of foreign exchange reserves in our country by offering their products to rest of the world and using less import intensive techniques.